2006
DOI: 10.1007/s00535-006-1790-5
|View full text |Cite
|
Sign up to set email alerts
|

Visceral fat accumulation and insulin resistance are important factors in nonalcoholic fatty liver disease

Abstract: The severity of fatty liver was positively correlated with visceral fat accumulation and insulin resistance in both obese and nonobese subjects, suggesting that hepatic fat infiltration in nonalcoholic fatty liver disease may be influenced by visceral fat accumulation regardless of body mass index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
211
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(240 citation statements)
references
References 28 publications
19
211
2
2
Order By: Relevance
“…40,41 Regardless of BMI, central adiposity has been shown to be associated with NAFLD in normal weight, obese and diabetic individuals. 17,42,43 As the presence of PHT is related to the degree of steatosis, and as the degree of steatosis is related to the amount of visceral fat, the predictive role of waist circumference can easily be understood. Even after correction for the degree of steatosis, however, waist circumference remains an independent predictor of PTH, indicating that the relation between waist and steatosis-associated PTH cannot be fully explained by steatosis alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,41 Regardless of BMI, central adiposity has been shown to be associated with NAFLD in normal weight, obese and diabetic individuals. 17,42,43 As the presence of PHT is related to the degree of steatosis, and as the degree of steatosis is related to the amount of visceral fat, the predictive role of waist circumference can easily be understood. Even after correction for the degree of steatosis, however, waist circumference remains an independent predictor of PTH, indicating that the relation between waist and steatosis-associated PTH cannot be fully explained by steatosis alone.…”
Section: Discussionmentioning
confidence: 99%
“…46,47,52 Previous studies showed that that the severity of fatty liver was positively correlated with visceral fat accumulation and insulin resistance. 42,48 However, the exact causal relation between IR, visceral fat and steatosis remains unclear. Furthermore, there are patients with IR and NAFLD who are not obese, indicating that other factors besides visceral obesity contribute to the association between NAFLD and IR.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kwon et al, found that the differences in the amount of visceral fat between individuals with NAFLD and those without NAFLD may be greater in the non-obese group than in the obese group (Kwon et al, 2012). This suggests that visceral fat could be used as an important predictive factor for the development of NAFLD (Eguchi et al, 2006).…”
Section: Nafld: the Liver Manifestation Of Metsmentioning
confidence: 99%
“…Plasma free fatty acids are largely released by white adipose tissue when insulin resistance develops. Indeed, insulin resistance in this tissue results in increased lipolysis, which leads to high levels of circulating fatty acids ( Fig.1) (Eguchi et al, 2006). Altogether, hepatic fat accumulation causes NAFLD, subsequently leading to hepatic insulin resistance.…”
Section: Insulin Resistance: a Critical Node Between Mets And Nafldmentioning
confidence: 99%
“…In accordance with our findings, a previous study performed in Japan demonstrated that the severity of fatty liver, assessed by ultrasonography, was correlated with visceral fat accumulation and insulin resistance. 14 Chronic ALT elevation is considered to be a marker of hepatocyte damage. Increased ALT activity was associated with the MS, and this association was graded across a number of metabolic components.…”
Section: Discussionmentioning
confidence: 99%